Combination Therapy with Acetaminophen and Ibuprofen for Patent Ductus Arteriosus in Extremely Preterm Infants: A Retrospective Study in South Korea - Kim, Eun Jin; Cho, Hye Jung; Beak, Gyeong Yoon; Jin, Wook; Son, Dong Woo (Perinatology (Online), 2024)
Objective: This study aimed to investigate the closure rate and adverse effects of combination therapy with acetaminophen and ibuprofen for hemodynamically significant patent ductus arteriosus (hsPDA) compared with monotherapy with ibuprofen in extremely preterm infants (EPTs). Methods: This was a single-center, retrospective, and historical control study of infants with hsPDA born at <28 weeks of gestation and a birth weight <1,000 g. Based on the first-line therapeutic policy for hsPDA, the cohort was classified into a monotherapy group (period I: January 2019-July 2021) and a combination therapy group (period II: September 2021-August 2023). Baseline characteristics, treatment outcomes, adverse effects, and morbidities were compared between the groups. Results: Of the 43 EPTs with hsPDA, 26 received monotherapy with ibuprofen during period I, and 17 received combination therapy with acetaminophen and ibuprofen during period II. The successful closure rates after the first medical therapy were 42.3% in the monotherapy group vs. 76.5% in the combination therapy group (P=0.027). No significant difference in adverse effects during medication use was observed between the groups. Conclusion: Combination therapy with acetaminophen and ibuprofen improved the closure rate for hsPDA without detectable adverse effects. Combination therapy could be considered the first therapeutic option for hsPDA in EPTs. Further well-designed studies are needed to define the safety and effectiveness of combination therapy. KCI Citation Count: 0